The relationship between body image and sexual performance and mental health in married housewives - Zarif, Pegah; Ghasemian, Ayoub (Psychology of Woman Journal, 2020)
This research investigated body image and its relationship with sexual performance and mental health in married housewives. The current research was descriptive and correlational. The research's statistical population was comprised of all married women who were housewives in Mashhad in 2019-2020. Among the statistical population, 450 people were selected and studied as available sampling. Goldenberg's mental health questionnaires (GHQ-28), Rosen et al.'s (1990), and body image of women (1990) were used to collect data. After collecting and extracting the data, the participants' scores were analyzed using Pearson correlation analysis and multiple and multivariable linear regression, and SPSS-24 statistical software. The Pearson correlation analysis results showed a positive and significant relationship between body image and sexual performance in married housewives (r=0.363). The component of satisfaction with different parts of the body showed the highest relationship and correlation with the total score of sexual performance in a positive and significant way (r=0.321). After that, the components of tendency about weight and the body showed a positive and significant relationship with the total score of sexual performance (r=0.301 and r=0.289). There is an inverse and significant relationship between body image and mental health in married housewives (r=0.281). The component of satisfaction with different parts of the body showed the highest inverse and significant relationship with the total (absence) score of mental health (r=0.225). After that, the components of the body itself (proportion) and attitude about weight showed an inverse and significant relationship with the total score (absence) of mental health (r=-0.196 and r=-0.171). Also, regression analysis showed that body image could predict sexual performance and mental health in married housewives.